630 Longer Sleep Duration Reduces the Odds of Hypertension in Children Referred to Nephrology for Elevated Blood Pressure. (3rd May 2021) - Kogon, Amy; Masqood, Anam; LoGuidice, Jillian; Myers, Kevin; Mitchell, Jonathan
Abstract: Introduction: Lifestyle modification is often prescribed as first line-therapy for hypertension in childhood. We aimed to determine if there was an association between sleep duration and hypertension in children referred for evaluation to Nephrology for elevated blood pressure (BP). We hypothesized that, longer sleep duration would be associated with a reduced likelihood of a hypertension diagnosis. Methods: Medical record data were retrospectively extracted from patients referred to the Children's Hospital of Philadelphia's pediatric nephrology clinic for the evaluation of elevated BP, without a prior hypertension diagnosis. Ambulatory blood pressure monitoring (ABPM) data collected between December 2015 to December 2018 were extracted. Hypertension was defined by ABPM according to American Heart Association recommendations for pediatric ABPM and we evaluated BP indexed to sex and height. Sleep duration was calculated as the difference between self-reported time of sleep onset and offset. Regression models were adjusted for age, sex, race, body mass index, and weeknight status. Results: Our sample included 249 patients, with a mean age of 14.5 (SD: 3.1) years. Of these, 29% were obese and 42% met criteria for hypertension. Mean sleep duration was 9.3 (SD: 1.6) hours per night and duration was shorter with increasing age in years (β=-0.11, 95% CI: -0.18, -0.05) and on week vs. weekend nights (β=-0.62, 95% CI: -1.05, -0.24). Each additional hour of sleep was associated with lower daytime systolic BP Index Z-score (β=-0.12, 95% CI: -0.20, -0.05), lower daytime diastolic BP Index Z-score (β=-0.11, 95% CI: -0.19, -0.03) and 19% reduced odds of daytime hypertension (OR=0.81, 95% CI: 0.67, 0.98). Each additional hour of earlier timing of sleep onset was associated with lower daytime systolic BP Index Z-score (β=-0.10, 95% CI: -0.19, -0.01), lower daytime diastolic BP Index Z-score (β=-0.16, 95% CI -0.25, -0.06) and 16% reduced odds of daytime hypertension (OR=0.84, 95% CI: 0.68, 1.05). Conclusion: In children referred for the evaluation of elevated BP, longer sleep duration and earlier sleep onset were associated with a reduced likelihood of being diagnosed with hypertension. Targeting improvements in sleep should be further investigated as part of first line therapy to treat pediatric hypertension. Support (if any): NIH/NHLBI K01HL123612